Integrasi Server On-Premise dengan Server Cloud Menggunakan Cloud VPN dan Mikrotik Ipsec Untuk Peningkatan Keamanan Koneksi - Hilmi Afifi Al-Atsari; Imam Suharjo (Syntax Corporation Indonesia, 2023)
In the ever-evolving digital era, integration of onpremise server infrastructure with cloud servers has become an important focus for many companies. The problem faced is regarding connections that use public IP addresses directly, which are often vulnerable to various security risks and cyber threats. Therefore, this research aims to identify and overcome the main problems that arise in this integration. With a better understanding of these challenges, developers and organizations can improve the security of their hybrid server infrastructure. The research methodology uses Mikrotik IPsec and VPN Tunnel IKEv2 on Google Cloud services. This approach is utilized to increase connection security between onpremise servers and cloud servers. First, the author configures Mikrotik IPsec on the onpremise server and sets up the IKEv2 VPN Tunnel on Google Cloud services. Next, the author carried out practical tests by sending data between the two infrastructures and monitoring the security and stability of the connection. With these steps, we can evaluate the effectiveness of security solutions implemented in a hybrid server environment. The research results show that this approach is successful in securing the connection between the two infrastructures, reducing potential risks such as sniffing, port scanning attacks, brute force, DDOS, and other cyber threats. Moreover, during practical trials, the connection remained stable and performed optimally, demonstrating the effectiveness of the proposed solution in improving the security of hybrid server infrastructure. These results can provide concrete evidence that using Mikrotik IPsec and VPN Tunnel IKEv2 on Google Cloud services can be an effective step in securing communications between onpremise servers and cloud servers. Thus, this research provides valuable guidance for developers and organizations looking to implement similar solutions.